DOP32 Long-term outcomes of enterocutaneous fistula complicating Crohn's Disease: The ECUFIT study from GETECCU. (27th May 2021) - Rodríguez-Lago, I; García Pérez, C; Calafat, M; Soto, M P; Calvo, M; Sánchez Rodríguez, E; Caballol, B; Vela, M; Rivero, M; Muñoz, F; De Castro, L; Calvet, X; et al.
Abstract: Background: Crohn's disease (CD) can develop fistulizing complications at any time during the disease course. Enterocutaneous fistulas (ECF) are disabling lesions with a significant impact on quality of life. The aim of this study was to describe the characteristics and natural history of ECF complicating CD, and to analyze its medical and/or surgical management. Methods: A retrospective analysis of all adult patients with fistulizing CD with at least one episode of ECF from the ENEIDA registry (over 68, 000 patients) was performed. ECF were defined as a communication between the gastrointestinal tract and the skin producing leakage of luminal contents. Additional data describing the ECF and its medical or surgical management were gathered. The main endpoint was any ECF-related surgical intervention. Fistula closure was defined as the absence of drainage, with no new abscess or surgery for at least 6 months. A comparison of the characteristics and outcomes after the availability of biologic agents (Jan/2000) was also performed. The baseline characteristics were analyzed by means of descriptive statistics and were compared by non-parametric tests. Factors associated with surgery were further evaluated in a binary multivariable regression and survival analysis. Results: A total of 301 ECF in 286 patients from 46 hospitals diagnosed between Jan/1970-Sept/2020 were included (median age 34 years (IQR, 27–46); 59% male; 67% L3). ECF had a median of 1 external opening (range 1–10), 59% with concomitant internal fistulas, and usually involved the ileum (67%) or colon (23%). After 146 months (IQR, 69–233) of follow-up, 37% received thiopurines, 40% anti-TNF, 6% ustekinumab and 2% vedolizumab. Surgery was performed in 208 patients (69%) after a median of 4 months (IQR, 1.4–12). Fistula closure was achieved in 253 patients (84%) after 30 months (IQR, 4–84), mostly after surgery (54%) and in one third after medical therapy. Fistula recurrence was uncommon (11%) after closure. Patient and fistula characteristics were significantly different after the availability of biologics. In fact, anti-TNF biologics and thiopurines reduced surgery risk (HR 0.5; 0.38–0.67; HR 0.64; 0.47–0.86, respectively). The surgery rate in the biologic era tends to be lower than before (OR 0.63;0.33–1.09) while timing is similar. Closure rates are also comparable, but it was obtained more frequently after medical therapy once biologicals were available (OR 2.21; 1.13–4.29). Conclusion: ECF complicating CD entail a high burden of medical and surgical resources. Closure rates are high, usually after surgery, and fistula recurrence is uncommon. A number of patients can benefit from medical therapy and achieve fistula closure.